Investigating the Relationship Between Perceived Community Safety and the Public's Attitudes Towards the Treatment of Youth Offenders in New Zealand. (17th August 2018) - McArdle, Sean; Lambie, Ian; Miers, Sarah
Abstract : While opinions on what should be done with youth offenders vary from person to person, perceived levels of safety and fear of crime have been linked to more punitive attitudes towards crime and punishment. Qualitative methods were employed to explore the attitudes and opinions of members of the New Zealand public with varying levels of community safety in respect to the treatment of youth offenders. Results indicate those who identified as lowest in levels of safety were more punitive in their opinions, though they also expressed a firm desire for progressive treatment options such as rehabilitation and taking preventative action. Those who felt the safest in their community were less likely to be punitive in their opinions towards youth offenders.